The essential guide to RTI : an Integrated, evidence-based approach - DeRuvo, Silvia L (San Francisco : Jossey-Bass, 2010)
'A practical, hands-on guide that helps teachers fulfill the promise of RTI Filled with practical tools and step-by-step guidelines, this book shows teachers how to implement RTI effectively. This valuable resource helps teachers assess a school's or classroom's readiness to begin the implementation process, and offers extensive resources to help educators identify appropriate screening and progress monitoring tools for students. DeRuvo provides dozens of effective research-based interventions and instructional strategies that teachers can implement immediately in their classrooms, and offers guidelines for selecting additional curricula and strategies to support students with diverse needs. Includes easy and efficient progress monitoring strategies to measure RTI effectiveness Written by veteran educator and active teacher trainer, Silva DeRuvo Provides helpful advice for effective collaboration between teachers The book includes strategies for joint curriculum mapping, as well as for measuring student mastery of identified content area standards.'--
Includes bibliographical references and index
Keywords: Remedial teaching -- Handbooks, manuals, etc; Slow learning children -- Education -- Handbooks, manuals, etc; Learning disabled children -- Education -- Handbooks, manuals, etc